2019
DOI: 10.1371/journal.pone.0211568
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological AMPK activation induces transcriptional responses congruent to exercise in skeletal and cardiac muscle, adipose tissues and liver

Abstract: Physical activity promotes metabolic and cardiovascular health benefits that derive in part from the transcriptional responses to exercise that occur within skeletal muscle and other organs. There is interest in discovering a pharmacologic exercise mimetic that could imbue wellness and alleviate disease burden. However, the molecular physiology by which exercise signals the transcriptional response is highly complex, making it challenging to identify a single target for pharmacological mimicry. The current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 59 publications
(76 reference statements)
0
24
0
1
Order By: Relevance
“…MK-8722 is a potent pharmacological activator of all 12 AMPK isoforms ( Myers et al., 2017 ; Muise et al., 2019 ). The compound directly binds to the allosteric drug and metabolite site located at the interface between the α-subunit kinase domain and the carbohydrate-binding module in the β-subunit, which is thought to protect Thr172 from dephosphorylation ( Steinberg and Carling, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…MK-8722 is a potent pharmacological activator of all 12 AMPK isoforms ( Myers et al., 2017 ; Muise et al., 2019 ). The compound directly binds to the allosteric drug and metabolite site located at the interface between the α-subunit kinase domain and the carbohydrate-binding module in the β-subunit, which is thought to protect Thr172 from dephosphorylation ( Steinberg and Carling, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetically, MG can stimulate AMPK activation via direct or indirect pathways. MG can increase the AMP-to-ATP ratio, a stimulus for AMPK, by decreasing the mitochondrial membrane potential and intracellular ATP levels [18][19][20]. AMPK can also be activated by oxidative stress via the classical AMP-mediated pathway [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, because these effects on heart weight are consistent with our previous experience in diabetic mouse models in which there was limited weight loss, it is reasonable to infer there may be a direct effect on heart (Myers et al, 2017; Muise et al, 2019). Interestingly, however, our laboratory recently reported that short-acting AMPK activators achieve transcriptional responses that are highly similar to those generated by longacting AMPK activators (like MK-8722) in skeletal and cardiac muscle, liver, and adipose tissue, though renal transcriptional responses were not assessed (Muise et al, 2019). Importantly, in those studies, the daily administration Fig.…”
Section: Discussionmentioning
confidence: 99%